Analysis of basic value levels of sport high school and general high school students according to receiving physical education and sports courses - Kanat, Metin; Savucu, Yüksel; Biçer, Yonca S.; Coşkuner, Zeki; Karadağ, Mustafa (My University, 2013)
The aim of this study was to analyze basic value level of Anatolian Sport High School and General High School students according to their receiving Physical Education and Sports courses. As 296 girls and 324 boys from General High School and 84 boys and 49 girls from Anatolian High School students, totally 753 students participated in research. In order to collect data related to independent and dependent variables, “Personal Information Form” and “Portrait Values Scale” were applied to high school students. Research data was evaluated by using Independent Sample T Test with statistics packet program. According to research results, meaningful difference in support of General High School was found at humanistic basic values which Power, Success, Excitement, Self-Management, Universalism, Benevolence, Compliance and Safety related to sub dimension according to Anatolian Sport High School and General High School students school types. Besides it was found that total points related to basic values vary according to gender and meaningful differences were found for the benefit of the girls. Meaningful differences were not found at Hedonism and Conventionalism sub levels.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Physical education and sports; Lesson; Basic value